Contestation for land towards Kampong Adat of Sakai Minas in Riau: - Marfuah, Istiqomah; Amady, Muhammad Rawa El (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2021)
This research discussed the Kampong Adat in Minas Barat Village, Minas District, Siak Regency. Regional Regulation Number 2 concerning the determination of Kampong Adat had issued since 2015. However, the completeness of requirements for the Ministry of Home Affairs approval has not been completed until November 2021. This study used an ethnography design; the researcher lived in the research site for two months. The data were collected by participatory observation, in-depth interviews with selected informants due to their knowledge and experience in the establishment of Kampong Adat. The data were analyzed descriptively by discussing with theory and resulted in the general trend as this research's findings. This research found, first, Since Minas Barat Village of determined as Kampong Adat, the community of Sakai Tribe have been minority citizen. Second, the Sakai community has some difficulties preparing the complete requirements for approval of the Ministry of Home Affairs because there are many interests involved in the village. Third, the government has not given severe attempts for Kampong Adat. The government let the completeness of approval has not yet been fulfilled for almost seven years. This study contributed to the anthropology of policy, specifically for indigenous peoples, in issuing affirmative policies to fulfill the rights of indigenous peoples.